2023
DOI: 10.1002/adem.202300447
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Investigation on Energy Absorption of Cu Casting Lattice Structure during Compression

Abstract: This investigation aims to assess the mechanical behavior and energy absorption properties of the Cu lattice structures made by investment casting method experimentally and by finite element method (FEM) simulation. The casting pattern of lattice structures is additively manufactured with 2.0, 2.5, and 3.0 mm diameters and the lattice structures produced by investment casting of Cu. Then a uniaxial compression test is applied to measure maximum compressive strength, energy absorption density, efficiency, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…According to ref. [47] and ISO 13 314, [ 55 ] in examining the mechanical properties of metal foams, the densification strain (εD$\left(\epsilon\right)_{\text{D}}$) is a significant factor as it ends the porous behavior and makes the material act like its bulk. Moreover, the plateau region of metal foams is the area of stress–strain graph that is responsible for the absorbed energy of these metallic foams.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to ref. [47] and ISO 13 314, [ 55 ] in examining the mechanical properties of metal foams, the densification strain (εD$\left(\epsilon\right)_{\text{D}}$) is a significant factor as it ends the porous behavior and makes the material act like its bulk. Moreover, the plateau region of metal foams is the area of stress–strain graph that is responsible for the absorbed energy of these metallic foams.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the increasing discrepancies between the prediction by the shock theory were due to the higher level of densification strain that can be achieved experimentally than is predicted analytically when using simple theories. Moreover, Rohani Nejad et al [ 47 ] produced a new generation of sandwich panels with open‐cell metal foam cores through additive manufacturing of polymers and electroforming of nickel and reported that the strength and energy absorption properties of these sandwich structures will increase by increasing the pores per inches (PPI) of these novel materials. Furthermore, Reda et al [ 20 ] produced a type of multilayer metal foam with unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the normalized stresses are a new approach that is used to better understand the mechanical response and characteristics of porous materials 36 . Equation ( 1 ), normalized the tolerated stresses to reach a better and comparative factor.…”
Section: Resultsmentioning
confidence: 99%